PERANCANGAN SISTEM INFORMASI PERMINTAAN BARANG DAN SUKU CADANG PADA PT. HAYATI PRATAMA MANDIRI BERBASIS WEB MENGGUNAKAN FRAMEWORK SCRUM - Masriadi, Masriadi; Ikhlas, Muhammad (Jurnal Ilmiah Sistem Informasi, 2023)
PT. Hayati Pratama Mandiri is a company and business engaged in the sale of Honda brand motorized vehicles. PT. Hayati Pratama Mandiri is the largest sales company for Honda motorcycles in West Sumatra, currently has several branches spread across various districts and cities in West Sumatra. In addition to selling various kinds of Honda motorcycles, this company also sells spare parts and repairs or service motorcycles. In terms of selling spare parts and requesting goods, PT. Hayati Pratama Mandiri is still having difficulties in making requests for goods and spare parts to the warehouse because there is no information system or website that can make it easier for branches and sales departments to make requests for goods and spare parts quickly. So that having a website requesting goods and spare parts can make it easier to distribute and request goods without having to wait and come to ask for approval of goods out to the leadership. Therefore we try to help build a website to overcome the problems that exist at PT. Hayati Pratama Mandiri